2020
DOI: 10.3389/fonc.2019.01517
|View full text |Cite
|
Sign up to set email alerts
|

UBASH3B Is a Novel Prognostic Biomarker and Correlated With Immune Infiltrates in Prostate Cancer

Abstract: Background: UBASH3B (STS1) is an important gene that negatively regulates T-cell receptor signaling in activated T-lymphocytes that involved in cancers. However, the function of UBASH3B in prostate cancer (PCa) and the correlation between UBASH3B and tumor-infiltrating immune cells still remain unclear. Methods: Real-time PCR and immunohistochemistry were applied to detect mRNA and protein expression of UBASH3B in PCa patients and benign prostate hyperplasia patients (BPH). Clinical features of patients with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 17 publications
(22 reference statements)
0
38
0
Order By: Relevance
“…Timer was used to analyze the tumor-infiltrating immune cells and the correlations between the infiltrating level of different subsets of immune cells and IGF2BP2 high and low expression samples. Cibersort was used for estimating the abundance of different immune cell types in tumor microenvironment by FPKM data [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Timer was used to analyze the tumor-infiltrating immune cells and the correlations between the infiltrating level of different subsets of immune cells and IGF2BP2 high and low expression samples. Cibersort was used for estimating the abundance of different immune cell types in tumor microenvironment by FPKM data [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Fortunately, a recent study by Chen and coworkers reported that the expression of miR-192-5p is aberrantly increased in prostate cancer tissues, and the enhanced expression of miR-192-5p promotes the proliferation of prostate cancer cells in vitro ( Chen ZJ et al, 2019 ). Additionally, bioinformatics analyses have revealed that miR-192-5p is associated with ubiquitin-associated and SH3 domain-containing B (UBASH3B), a poor prognostic marker of prostate cancer ( Wang et al, 2019 ). These two studies reveal the possible regulatory role of miR-192-5p in prostate cancer.…”
Section: Mir-192-5p In Human Diseasesmentioning
confidence: 99%
“…Compared with the other clusters, the MP cluster exhibited MC-like development features, such as high expression of STAT5A/STAT5B , SRGN , MAPK14 , and MITF ( Shelburne et al, 2003 ; Abrink et al, 2004 ; Morii et al, 2004 ; Hu et al, 2012 ). Furthermore, several genes related to MC activation, including FCER1G , UNC13D , CD84 , CD226 , LCP2 , STXBP2 , and BTK , were highly expressed in this cluster ( Figure 3B; Bachelet et al, 2006 ; Álvarez-Errico et al, 2011 ; Oksaharju et al, 2011 ; Bin et al, 2013 ; Rodarte et al, 2018 ; Simonowski et al, 2020 ; Wang et al, 2020 ). However, in this cluster, the endothelial markers PECAM1 and ITGB3 were highly expressed, while the hematopoietic markers SPN and PTPRC were weakly expressed and absent, respectively ( Supplementary Figure S3D ).…”
Section: Resultsmentioning
confidence: 94%